Time & Truth with Frida Buhre and Eric Bengtson (Sweden) - Bjork C; Quintero J; Buhre F; Bengtson E (Global Rhetorics podcast, 2020)
Producer-hosts Dr Collin Bjork and Jose Quintero host the first of a two-part interview with Dr. Frida Buhre and Dr. Erik Bengtson, both scholars at Uppsala University in Sweden. They tackle rhetoric’s relationship with two big ideas: time and truth. They also discuss the next generation of rhetorical scholarship in Sweden.